Studi Literatur: Perencanaan Sarana dan Prasarana Pendidikan - Ningsih, Auliya Cahya; Silalahi, Elsa; Ramadhanti, Alikha; Rahmadani, Leni; Izandy, Cahaya Rahma; Ratnadila, Nurul (Jurnal Ilmiah Dikdaya, 2024)
This research uses a literature review method or literature study, which is an article or book compiled based on a literature search, both national and international. The conclusion of this research is that planning educational facilities and infrastructure is to avoid unwanted errors and failures and to increase effectiveness and efficiency in its implementation